Blood pressure-lowering effect of nebivolol in hypertensive patients with type 2 diabetes mellitus. The YESTONO Study - A. C. Schmidt; Ch. Graf; K. Brixius; J. Scholze (Кардиоваскулярная терапия и профилактика)
Background: Effective blood pressure (BP) lowering therapy is regarded as the most important intervention in diabetes mellitus (DM). Nebivolol is commonly used for the treatment of hypertension (AH), but to date there has been no study of its use in a large population of hypertensive patients with type 2 diabetes mellitus (DM-2). Methods: A prospective, open-label, multicentre, post-marketing surveillance study was conducted in 2838 patients with AH requiring intervention and concomitant DM-2, with or without other diseases. The therapeutic agent was nebivolol, either as monotherapy or as add-on therapy to other antihypertensive agents, over a minimum period of 3 months, with the primary endpoint being achievement of target BP, that is, systolic BP ≤140 mm Hg and diastolic BP ≤90 mm Hg. Other endpoints were changes in metabolic parameters, effects on physical capability and tolerability during treatment. Statistical analysis was prospectively planned and conducted on an intention-totreat basis. Results: Mean (SD) BP decreased from 156 (15,3)/92 (9,4) mm Hg to 135 (11)/81 (6,6) mm Hg during the treatment period, while mean (SD) heart rate decreased from 79 (10) to 71 (7) beats/min. Strict reduction of BP was associated with improvements in most metabolic parameters, including lipid levels, glycosylated haemoglobin (HbA1c), and microalbuminuria. Maximum physical capability improved modestly. Most patients (85%) received nebivolol 5 mg/day. Conclusions: Strict BP reduction in AH patients with DM-2, with or without other concomitant diseases, is achieved with nebivolol 5 mg/day in most patients. The benefits of lowering BP with use of nebivolol are associated with improvements in most metabolic parameters and in maximum physical capability.